Bound to Interpret: Russia, NATO, and the Military-Political Crises in the Post-Cold War Order - N. Ya. Neklyudov (Международная аналитика)
The study of Russia’s foreign policy poses something of a paradox. On the one hand, Russia’s actions are viewed as aimed at revising the existing rules-based order built by the end of the Cold War. On the other hand, on numerous occasions, one pinpoints that Russia has devised a language similar to the Western nations to justify its foreign policy. I call the phenomenon that explains this paradox the game of interpretation. The article illustrates how Russia is engaged in the game of interpretation with the West in the post-Cold War order by Russia’s appliance to the norm of humanitarian interventions. By analyzing the Russian discourse during the Russo-Georgian War (2008), I demonstrate how the Russian foreign policy leadership reproduces similar narrative patterns used by the West during the Kosovo War (1999). Exemplifying the game of interpretation by humanitarian interventionism is not accidental. Humanitarian interventionism is studied in the literature as being characteristic of the Western ‘ethical foreign policy’ originated by the end of the Cold War, with Russia being depicted as either skeptical or as an unequivocal opponent of such an approach in world politics. Methodologically, the work builds on quantitative and qualitative analysis of selected texts compiled from the archives of NATO and the US State Department, as well as the website “Kremlin.ru” and the website of the Russian Foreign Ministry.